Factors Associated with Diabetic Retinopathy in Chinese Patients with Type 2 Diabetes Mellitus - Bin-Bin He; Li Wei; Yun-Juan Gu; Jun-Feng Han; Ming Li; Yu-Xiang Liu; Yu-Qian Bao; Wei-Ping Jia (International Journal of Endocrinology)
Objective. To investigate the risk factors of DR in Chinese T2DM patients. Methods. 2009 patients with T2DM were included in this cross-sectional study. All patients underwent eye examination, and the DR stage was defined by an ophthalmologist. Correlation analysis was performed to evaluate the relation between DR and clinical variables. Logistic regression models were used to assess risk for those factors associated with DR. Results. A total of 597 T2DM patients (29.7%) had DR, of which 548 (27.3%) were nonproliferative diabetic retinopathy and 49 (2.4%) were proliferative diabetic retinopathy. Positive correlations were found between DR and duration of diabetes, systolic blood pressure (SBP), diastolic blood pressure, glycated hemoglobin, glycated albumin, 24 hurinary albumin excretion, peripheral atherosclerosis (PA), diabetes nephropathy (DN), diabetic peripheral neuropathy, and anemia. Negative correlations were found between DR and C-peptide and glomerular filtration rate. Logistic regression analysis revealed that duration of diabetes, SBP, DN, anemia, PA, and C-peptide were each independent risk factors of DR. Conclusion. The duration of diabetes, SBP, DN, anemia, and PA are positively associated with DR in Chinese T2DM patients, while C-peptide is negatively associated with DR. Monitoring and evaluation of these related factors will likely contribute to the prevention and treatment of DR.